Effect of interactions between nitrogen fertilizer (urea) and time periods on the growth of algae Chroococcus sp. - Fadhel Khalef, Wesan (University of Thi-Qar Journal of Science, 2019)
This study included isolating, diagnosing and puriflying algae Chroococcus sp. (Blue - green algae) was collected from Al-Garraf River and cultured on ( Ch-10) media (3,5and10)% urea was added in three concentration in addation to control treatment. This study showed the effect of urea fertilizer on the growth rate of algae the use of urea has led to variability in the number of cell in algae . An increase in the numbers was observed in the first, second and third stage of growth.where recorded low numbers in the fourth and fifth stage of growth. The results showed that the lowest value recorded of Chroococcus was 30 (cells / 100 ml )in the ninth day while largest value was 650 (cells / 100 ml) on the fifth day.